Cultivation of Chinese-to-Foreign Translation Talents in the Context of New Liberal Arts - Quan, Jigang (Pacific International Journal, 2024)
Under the background of new liberal arts, the cultivation of Chinese-to-foreign translation talents faces new opportunities and challenges. This study systematically analyzes the current status and problems of the cultivation of Chinese-to-foreign translation talents through methods such as questionnaire surveys and in-depth interviews, and proposes corresponding improvement strategies. The research finds that the current cultivation of Chinese-to-foreign translation talents has problems such as monotonous curriculum settings, conservative teaching methods, and insufficient practical teaching, which are difficult to meet the diverse needs for translation talents under the new liberal arts background. In response to these problems, this study suggests starting with optimizing the curriculum system, innovating teaching methods, and strengthening practical teaching to construct a cross-disciplinary integration, practice and innovation-oriented Chinese-to-foreign translation talent cultivation model. At the same time, the study also emphasizes the key role of teachers in the cultivation process, proposing to promote the overall improvement of the teacher team through enhancing teachers' professional quality and strengthening teacher training. In addition, this study also pays attention to the latest trends and market demands of the translation industry, and proposes a cultivation strategy that combines the concept of new liberal arts with market demands, aiming to cultivate more Chinese-to-foreign translation talents with innovative spirit, practical ability, and cross-cultural communication skills.